Institutional purchases program in Costa Rica: Productive policy questioned but socially necessary - Díaz Porras, Rafael Antonio (2020)
The PAI is a program aimed at creating and promoting a market for small agricultural producers through state institutions´ purchases that also fits into public policies for the strengthening of Food and Nutrition Security Policies (FNSP). The analysis is done by reviewing the arguments that justify the intervention of the state, the objectives pursued, and the failures in the execution of the policy. The PAI is a socially desirable policy to promote the production of small producers and through it, to support rural development and food security, but which, by its very nature, is a program that involves high degrees of difficulty to be simultaneously an instrument of productive promotion and institutional supply. The article addresses the various critical aspects faced and based on the specific analysis of the provision of horticultural products by the EPI, determines critical points of the system, with special attention to safety management. It concludes by arguing that the alternative of using market mechanisms could satisfy the requirements of institutional clients but would not guarantee the participation of small producers. Therefore, it is essential to face the critical points surrounding the program.